Il movimento Slow Food: Narrative di un fenomeno postmoderno - Gianni Cicia; Anna Russo Spena; Luigi Mennella (Italian Review of Agricultural Economics (REA), 2021)
– The Slow Food movement was born in 1986 as a protest movement against the macdonaldization of the agri-food system, then has progressively expanded in a new model of life: the slow-life. Starting from agriculture, the slow-life has established in many fields as an antagonist to the capitalist fast-life. It has been the subject of numerous criticisms which highlighted the existent contradictions. The worldwide growth of this movement has attracted the attention of scholars over the years. In the period 1992-2018 we found 641 papers dealing with the different aspects of Slow Food. At present, there is a lack of literature reviews on this scientific production. In this paper we have focused our attention on 47 papers that specifically analyse the Slow Food Movement to explain: 1) what kind of movement is Slow Food; 2) which impact had on the global agricultural system; and 3) how does it fit within the postmodern paradigm.This narrative review has highlighted how the Slow Food Movement is interpreted both as an Anti-globalizationand an Eco-gastronomic movement. The impact it has had on the agri-food system is certainly high but there is not a wide consensus about it. Finally, the Slow Food Movement appears clearly as a prominent expression of the postmodern paradigm.
Keywords: P36; Z13; 330; Slow Food; narrative review; postmodern society; social movement; consumer society